Evaluation of the GENE-UP ®E. coli O157:H7 Method for the Detection of E. coli O157:H7 in Select Foods: Collaborative Study, 2019.03. (13th June 2020) - Johnson, Ronald; Mills, John; Pittet, Jean-Louis; Rannou, Maryse; Bird, Patrick; Nelson, Maria
Abstract: Background: The GENE-UP ® E. coli O157:H7 2 (ECO 2) assay ( Performance Tested Method SM 121805) incorporates Fluorescence Resonance Energy Transfer hybridization probes into its proprietary PCR technology for the rapid detection of E. coli O157:H7 in select foods. Objective: The purpose of this validation was to evaluate the method's interlaboratory performance and submit the result to AOAC INTERNATIONAL for adoption as First Action Official Method SM for the detection of E. coli O157:H7 in select foods. Method: The GENE-UP ® method was evaluated in a multi-laboratory study as part of the MicroVal validation process using unpaired test portions for one food matrix, raw milk cheese (Comté, 34% fat, 0.8% salt). The candidate method was compared to the ISO 16654:2001 reference method. Fourteen participants from 13 laboratories throughout the European Union participated. Three levels of contamination were evaluated: a non-inoculated control level (0 colony-forming units (CFU)/test portion), a low contamination level (∼5 CFU/test portion), and a high contamination level (∼10 CFU/test portion). Data from that study were analyzed according to the Probability of Detection (POD) statistical model as presented in the AOAC validation guidelines. The difference in laboratory POD (dLPODC ) values with 95% confidence interval across collaborators was calculated for each level between the candidate and reference method results, and between the candidate presumptive and confirmed results. Results: The dLPODC values with 95% confidence interval were; 0.00 (–0.04, 0.04), 0.27 (0.04, 0.49), and 0.17 (0.01, 0.33) for the non-inoculated, low and high contamination levels respectively. Conclusions: The dLPODC results indicate a significant difference between the candidate method and the reference method for both the low and high contamination levels, with the candidate method producing higher recovery of the target organism at both levels. Highlights: The GENE-UP E. coli O157:H7 assay provides industry with a rapid, accurate detection method for E. coli O157:H7 in a broad range of foods.